1995
DOI: 10.1007/bf03015098
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with removal of the laryngeal mask airway: A comparison of removal in deeply anaesthetised versus awake patients

Abstract: Complications associated with removal of the laryngeal mask airway: a comparison of removal in deeply anaesthetised versus awake patientsThe purpose of the study was to compare the incidence of complications (coughing, biting, retching, vomiting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
45
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 11 publications
(9 reference statements)
1
45
0
Order By: Relevance
“…Previous studies showed that the incidence of complications associated with removal of the laryngeal mask was greater in awake patients than in anaesthetised patients [4][5][6][7]. However, the mask was removed apparently too early in 'awake' patients in some studies [5,7].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed that the incidence of complications associated with removal of the laryngeal mask was greater in awake patients than in anaesthetised patients [4][5][6][7]. However, the mask was removed apparently too early in 'awake' patients in some studies [5,7].…”
mentioning
confidence: 99%
“…Several anaesthetists compared the incidence of complications associated with the removal of the laryngeal mask between 'anaesthetised' and 'awake' states of the patients and reported that the incidence was greater when the mask was removed in 'awake' patients than in 'anaesthetised' patients [4][5][6][7]. However, in none of these studies, did they follow the method of removal in 'awake' patients, which is described in the instruction manual: in some studies, the mask was removed when the laryngeal reflexes or swallowing had returned, but before the patient had regained consciousness [4,5,7].…”
mentioning
confidence: 99%
See 3 more Smart Citations